2009
DOI: 10.3748/wjg.15.942
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-receptor blockers as therapy for mild-to-moderate hypertension-associated non-alcoholic steatohepatitis

Abstract: AIM:To evaluate insulin resistance, cytolysis and nonalcoholic steatohepatitis (NASH) score (NAS) using the Kleiner and Brunt criteria in 54 patients with NASH and mild-to-moderate hypertension, treated with telmisartan vs valsartan for 20 mo. METHODS:All patients met the NCEP-ATP Ⅲ criteria for metabolic syndrome. Histology confirmed steatohepatitis, defined as a NAS greater than five up to 3 wk prior inclusion, using the current criteria. Patients with viral hepatitis, chronic alcohol intake, drug abuse or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 64 publications
2
127
1
2
Order By: Relevance
“…In another RCT on hypertensive NAFLD patients, losartan plus simvastatin significantly improved ultrasonographic steatosis, visceral adiposity, HOMA and CRP compared with amlodipine plus simvastatin, despite similar BP reduction [76] (ESM Table 4). …”
Section: Angiotensin Receptor Blockersmentioning
confidence: 99%
“…In another RCT on hypertensive NAFLD patients, losartan plus simvastatin significantly improved ultrasonographic steatosis, visceral adiposity, HOMA and CRP compared with amlodipine plus simvastatin, despite similar BP reduction [76] (ESM Table 4). …”
Section: Angiotensin Receptor Blockersmentioning
confidence: 99%
“…An HQ RCT (quality score 7) randomized 54 hypertensive NASH patients to 20 months of valsartan or telmisartan (an angiotensin receptor blockers with PPAR-c-modulating activity). 61 Both agents improved steatosis; telmisartan significantly improved ballooning, lobular inflammation, and fibrosis compared with valsartan (Figs. 2-4).…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…After this pilot study, many animal and in vitro studies confirmed the beneficial efficacy of ARBs against NASH, but clinical studies were very limited. Only one RCT was published in 2009 [98]; however, this RCT was conducted with two treatment groups, and each group of patients was given a different ARB. This RCT reported that both telmisartan and valsartan have beneficial efficacy against NASH, but there was no placebo treatment group [98].…”
Section: Metformin Cq: Are Biguanides Effective For Patients With Nafmentioning
confidence: 99%
“…Only one RCT was published in 2009 [98]; however, this RCT was conducted with two treatment groups, and each group of patients was given a different ARB. This RCT reported that both telmisartan and valsartan have beneficial efficacy against NASH, but there was no placebo treatment group [98]. Thus, it is difficult to assess whether the beneficial efficacy against NASH is specific to ARBs or whether other antihypertensive agents might also have the same effect on NASH.…”
Section: Metformin Cq: Are Biguanides Effective For Patients With Nafmentioning
confidence: 99%